The Rayleigh prolongation factor at small bubble to wall stand-off distances - Reuter, Fabian (2022)
The Rayleigh collapse time is the time it would take to shrink an empty spherical bubble in an infinite liquid domain to zero size, which is a function of ambient pressure and initial bubble radius. If a solid boundary is located in the vicinity of the shrinking or collapsing bubble, then liquid flow is hindered, such that the collapse time is prolonged. This can be quantified with the Rayleigh prolongation factor. Here, we provide for intermediate to smallest bubble to wall stand-off distances. It is measured with single laser-induced cavitation bubbles in water close to a solid boundary. Maximum bubble radii are determined from microscopic high-speed imaging at one million frames per second. Collapse times are measured acoustically via the acoustic transients emitted during bubble seeding and collapse. The experimental findings are compared, with good agreement, to numerical simulations based on a volume of fluid method. As a result, a polynomial fit of versus stand-off distance is given for the near-wall bubble collapse in water. Then the influence of the viscosity on is studied numerically in the near-wall regime.